Rutting Resistance of Cold Bituminous Emulsion Mixtures (CBEMs) with Acrylic (AR) Polymer (Journal of University of Babylon for Engineering Sciences, 2018)
Rutting is one a distress that commonly occurs in flexible pavement, mainly due to exceedingly heavy axle loads, high ambient temperature, and insufficient paving materials quality. Dealing with the last reason of rutting, the paper aims at investigating rutting resistance of Cold Bituminous Emulsified Mixture (CBEMs) with Acrylic (AR) polymer. CBEMs were prepared with Ordinary Portland Cement (OPC) and conventional mineral filler (CMF) as a filler for its recognition benefit when introduce to CBEM.  Acrylic (AR) polymer emulsified was added to a cationic medium setting emulsified bitumen, with various dosages ranged from 0% to 5% of residual bitumen, to obtain a modified asphalt emulsion that was mixed with a local aggregate in order to prepare CBEMs. Also, it is intended to make a comparison between CBEMs, for the same circumstances of local aggregates and different types of filler, with the Hot Mix Asphalt (HMA).Marshall test is conducted to investigate the stability and flow of different mixes in the scope of the research. Further, Wheel track device connected to a computer system is used to measure rutting depth that indicates the expected rutting resistance. The results demonstrated a significant effect for AR polymer adding, where the rutting resistance for CBEMs comprising OPC is improved for almost all dosages, but the 1.25% recorded as the best one. It is worth to mention that the new polymer modified CBEM offers rutting resistance better than that of HMA, which sustain the possibility of replacing the common environment harmful paving technology by sustaining one.